2021
DOI: 10.3389/fpsyg.2021.661557
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Modeling on Self-Efficacy and Flow State of Adolescent Athletes Through Role Models

Abstract: This study aimed to verify the effects of role modeling on adolescent athletes’ self-efficacy and flow state. The subjects were middle school and high school athletes registered with the Korean Sport & Olympic Committee. From the collected data, descriptive statistics, confirmatory factor analysis, correlation analysis, and structural equation model analysis were performed. To verify the mediating effects of self-efficacy in the relationship between modeling and flow state, structural equation modeling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Support from peer interaction is important in establishing a positive attitude and increasing self-confidence and the ability to make judgments in learning ( Chu and Chu, 2010 ), while imitation from peer interaction contributes to the development of adolescents’ cognition, emotion, and behaviors. It is reported that adolescents accept the influence of role models in peer imitation to promote the development of their self-efficacy ( Lee et al, 2021 ). In addition, peer collaboration exerts an influence on self-efficacy ( Lee and Evans, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Support from peer interaction is important in establishing a positive attitude and increasing self-confidence and the ability to make judgments in learning ( Chu and Chu, 2010 ), while imitation from peer interaction contributes to the development of adolescents’ cognition, emotion, and behaviors. It is reported that adolescents accept the influence of role models in peer imitation to promote the development of their self-efficacy ( Lee et al, 2021 ). In addition, peer collaboration exerts an influence on self-efficacy ( Lee and Evans, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…The second reason why role modeling is an optimum strategy for SRL skills is that, as Bandura (1997) stated, this method provides vicarious experience. To illustrate, the students experienced Greta Thunberg's struggle to protect the environment (L7 & L16), the founder of the country's passion for reading (L4) and Teacher Danny's project to help street animals (L8), which made them appreciate other people's successes and want to perform like them (Lee et al, 2021). That vicarious experience also helped reduce students' stress and led to successful emulation of the role models (Schunk, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…The more the similarity, the more the model people persuade them to do the same. A study of Lee et al, (2021) proves that role-modelling gives positive effect on the ability of the flow state. Verbal persuasion is strengthening one's belief that one can succeed.…”
Section: Introductionmentioning
confidence: 89%